Evaluation of Quantity and Hyperhydricity of Cocoa Somatic Embryo Obtained from Solid Culture, Liquid Culture, and Sequence Subculture - Sulistyani Pancaningtyas (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Research  aimed  to  study  the  effect  of  solid  culture,  liquid  culture,  and sequence  subculture  on  quantity  and  hyperhydricity  of  somatic  embryo  wascarried  out  at  Laboratory  of  Biotechnology,  Indonesian  Coffee  and  Cocoa Research  Institute.  Materials  used  in  this  study  were  embryogenic  callitransferred  on  somatic  embryos  expression  both  in  solid  and  liquid  media with  the  same  media  composition,  namely  MS  medium  with  the  addition  ofAdenine  (0.025  mg/L).  Gelling  agent  used  in  solid  media  was  gelrite  (3  g/L). Clones used in this study was Sca 6. This research consisted of two trials, namely1)  effect  of  medium  type  (solid  and  liquid),  and  2)  sequence  subculture  (four subcultures).  This  results  showed  that  the  production  of  somatic  embryosin  liquid  medium  was  higher  than  in  the  solid  medium.  Regeneration  of somatic  embryos  on  solid  medium  culture  showed  the  highest  percentage  of abnormality  embryos  due  to  hyperhydricity  at  the  cotyledonary  phase  60%. Meanwhile,  the  regeneration  of  somatic  embryos  in  liquid  culture  showed the  highest  percentage  of  abnormality  embryos  due  to   hyperhydricity  at the  globular  and  cotyledonary  phase  37%.  Frequent  subculture  increased abnormal embryos  and  decreased  the  number of  somatic  embryos.Key words: Cacao, hyperhydricity,  somatic embryos,  solid  culture,  liquid  culture,  subculture,  in  vitro.